Effects of indium segregation and strain on near-infrared optical absorption in InGaN/GaN quantum wells - El Ghazi, Haddou; En-nadir, Redouane; Basyooni-M. Kabatas, Mohamed A.; Ibrahim, Jamal Eldin F. M.; Sali, Ahmed (Frontiers in Nanotechnology, 2024)
In this study, we present a novel numerical model that incorporates the effects of spontaneous and piezoelectric polarization-induced electric fields, along with multiple intersubband transitions, to investigate the optical absorption characteristics of InGaN/GaN strained single and double quantum well's structures. Focusing on the role of Indium surface segregation (ISS) in polar QW structures, we examine its influence on intersubband transition-related optical absorption and the resulting spectral behavior. Specific structural configurations are designed to achieve fourenergy-level with single and double quantum wells, optimized for three-color absorption within the near-infrared range. Our findings reveal that the combined impact of ISS and strain induces a notable red shift in the absorption spectra, with shifts varying significantly across different intersubband transitions. These findings underscore the potential of strained InGaN-based semiconductor compounds for developing advanced multi-color photonic devices, including near-infrared photodetectors and lasers, by harnessing their tunable optical properties.